Legislation of house of representatives performance highlights - Azed, Abdul Bari (2012)
House of Representatives carries out the mandate of the people through the legislative function, and established the Act with the consent of the President.People's expectations are optimal fulfilled by the House of Representative due to the less performance of Parliament in the legislation satisfactory because it does not reach the target of Prolegnas (National Legislative Program).This condition causes the functions of the House of Representatives as a parliament less than the maximum in promoting people's welfare and progress of the country.It is important to do a series of policies and concrete measures in order to minimize problems faced by parliament in order to encourage performance of the House of Representatives improvement in the legislative function.